Antimicrobial and Gtase Inhibitory Activity of Crude Methanol Extracts of Plants from Java and Kalimantan - Harlinda Kuspradini; Irmanida Batubara; Tohru Mitsunaga (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Some methanol extracts from Java and Kalimantan plants species were evaluated for in vitro anti-streptococcus sobrinus and Glucosyltransferase (GTase) inhibitory activity. The extracts were screened for anti-S. sobrinus and its related enzyme activity by broth dilution method.   IC50     and GTase were determined wherever activity was notice. The results revealed that the amount of phenolic and flavonoid compound varies from different plant species and the type of plant material (woody or herb). Out of 24 plant species, 9 species from methanol extracts showed good antibacterial activity in a range at 10 µg ml-1≤ IC50 ≤ 100 µg ml-1. The Intsia palembanica extract is the most antimicrobial. However, only 4 plants could exhibit GTase activity in a range at 18 µg m1-1 ≤ IC50  ≤50 µg ml-1. The most active extract is Psidium guajava (15.33 µg ml-1). The result of the present study suggests that some Indonesian plant can prevent dental caries and periodontal diseases, since it demonstrated antimicrobial and GTase inhibitory activity against S. sobrinus.